FAKTOR-FAKTOR PENENTU DALAM HARGA SAHAM PERUSAHAAN PROPERTI - Rizqi, Reza Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The goal of this research was to determine if ROA, NPM, and DER play a role in the stock price formation process in the real estate industry from 2017-2021. Inductive, quantitative, and descriptive features all play a role in the research technique. Thirty firms listed in IDX's property sector match the requirements for inclusion in the sample, which was selected using a purposive selection method. Using a Partial Least Squares (PLS) model for data analysis on a Structural Equation Model (SEM). SmartPLS 3.0 was utilized to perform the PLS analysis. Based on the findings of this study, it can be concluded that ROA and NPM have a positive and negative influence on stock prices, respectively, but DER has no effect on stock prices. Rate of return, net profit margin, and dividend yield all have a role in determining stock prices. The corrected R2 value shows that this component explains 15.7% of the variance, while the remaining 84.3% is accounted for by independent variables.